The Design and Construction of a Big Data System for Water Resource Warning and Forecasting in Vietnam - Loi, Nguyen Van; Tuan, Le Anh; Thinh, Tran Duc; Trung, Dang Tran (European Journal of Science, Innovation and Technology, 2024)
The study in this paper introduces the importance of a big data system in water resource forecasting, helping to mitigate the damage caused by natural disasters. With increasing demand for observational data and water resource forecasting information, the paper emphasizes the need to improve forecasting technology to provide accurate and timely information. The paper provides an overview of Big Data technology, including large data volumes, fast processing speeds, data diversity, and reliability. The architecture of the Big Data system at the Center for Water Resource Forecasting and Warning is designed with multiple components such as data sources, storage systems, batch processing, and real-time processing. Technologies like Hadoop and HDFS are applied to manage and store distributed data, ensuring data safety and recovery.The paper also proposes storage infrastructure and data analysis tools such as Hadoop, Apache Spark, along with security measures like data encryption and access control. Finally, the authors emphasize that the application of Big Data in water resource forecasting in Vietnam requires significant investment in infrastructure, technology, and specialized personnel.